The ALMA survey to Resolve exoKuiper belt Substructures (ARKS): VIII. A dust arc and non-Keplerian gas kinematics in HD 121617 - Perez-Marquez, S (EDP Sciences, 2026)
Context. ExoKuiper belts around young A-type stars often host CO gas, whose origin is still unclear. The ALMA survey to Resolve exoKuiper belt Substructures (ARKS) includes six of these gas-bearing belts, to characterise their dust and gas distributions and investigate the gas origin. Aims. As part of ARKS, we observed the gas-rich system HD 121617 with a 0″ 12 (14 au) resolution and discovered an arc of enhanced dust density. In this paper, we analyse in detail the dust and gas distributions and the gas kinematics of this system. Methods. We extracted radial and azimuthal profiles of the dust (in the millimetre and near-infrared) and gas emission (12CO and 13CO) from reconstructed images. To constrain the morphology of the arc, we fitted an asymmetric model to the dust emission. To characterise the gas kinematics, we fitted a Keplerian model to the velocity map and extracted the gas azimuthal velocity profile by deprojecting the data. Results. We find that the dust arc is narrow (1-5 au wide at a radius of 75 au), azimuthally extended with a full width at half maximum of ∼90°, and asymmetric; the emission is more azimuthally compact in the direction of the system s rotation, and represents 13% of the total dust mass (0.2 M⊕). From analysis of the scattered light and CO images, we conclude that the arc is much less pronounced or absent for small grains and gas. Finally, we find strong non-Keplerian azimuthal velocities at the inner and outer wings of the ring, as was expected due to strong pressure gradients. Conclusions. The dust arc resembles the asymmetries found in protoplanetary discs, often interpreted as the result of dust trapping in vortices. If the gas disc mass is high enough (≳20 M⊕, requiring a primordial gas origin), both the radial confinement of the ring and the azimuthal arc may result from dust grains responding to gas drag. Alternatively, it could result from planet-disc interactions via mean motion resonances. Further studies should test these hypotheses and may provide a dynamical gas mass estimate in this CO-rich exoKuiper belt. © The Authors 2026.